1992
DOI: 10.1111/j.1348-0421.1992.tb02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Pseudomonas pseudomallei Exotoxin and Whole Cell Antigens in Military Personnel in Sabah and Sarawak, Malaysia

Abstract: Sera from 420 military personnel serving in Sabah and Sarawk, Malaysia, were tested for antibodies to Pseudomonas pseudomallei exotoxin and whole cell antigens by enzyme-linked immunosorbent assay procedure (ELISA). Data showed that 54.4% of serum samples were positive for antibodies to P. pseudomallei exotoxin and 65.7% were positive for antibodies to the whole cell antigens. Samples gave much lower titers for anti-exotoxin antibodies compared to titers against crude whole cell antigens. The incidence of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Serosurveillance data on multiple population groups from 1969 reported a seroprevalence of 1.9 to 15.8% (91). A 1992 survey of army personnel in Sabah and Sarawak reported a prevalence of up to 65.7% (92). Notably, these studies appear to have included predominantly men and used different serological assays (91,92).…”
Section: Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Serosurveillance data on multiple population groups from 1969 reported a seroprevalence of 1.9 to 15.8% (91). A 1992 survey of army personnel in Sabah and Sarawak reported a prevalence of up to 65.7% (92). Notably, these studies appear to have included predominantly men and used different serological assays (91,92).…”
Section: Southeast Asiamentioning
confidence: 99%
“…A 1992 survey of army personnel in Sabah and Sarawak reported a prevalence of up to 65.7% (92). Notably, these studies appear to have included predominantly men and used different serological assays (91,92). Melioidosis is thought to account for approximately 2,000 deaths annually in Malaysia, which surpasses the mortality rates of both dengue and tuberculosis infections (93).…”
Section: Southeast Asiamentioning
confidence: 99%
“…Sarawak, in Malaysian Borneo, is endemic for melioidosis; although data have largely been limited to seroprevalence studies and case reports in adults [15, 16]. Of note, a recent study from Central Sarawak reported an unusually high isolation rate of gentamicin-susceptible B .…”
Section: Introductionmentioning
confidence: 99%
“…However, the UMC082 was a new infection, which was probably acquired during his vacation in Sabah. Cases have been reported in adults from Sabah, and a sero-prevalence study of military personnel in Sabah found that almost 60% had antibodies to B.pseudomallei [ 16 ]. Or it could also be possible that the patient was infected with two (or possibly more) strains during the original infection event, but due to minimal sampling and culturing efforts, this mixture was not detected until ST1644 was identified one year later.…”
Section: Discussionmentioning
confidence: 99%